PERIPHERAL CHEMICAL-REACTIONS - Bennun, M; Brouard, M; Simons, J; Levine, R (1993)
Forward scattering of the products of direct exoergic atom transfer reactions is proposed as an indication for a peripheral attraction: a reaction in which an atom at the periphery of the reactants is abstracted. Model computations for the O(1D) + N2O reaction are used to illustrate the proposed mechanism. The opacity function has a peak at higher impact parameters which is correlated with the forward scattering. Potential energy surfaces which do not manifest peripheral attraction lead to backwards scattering of the products. © 1993.